Desain Alat Press Kaleng Minuman Portabel Berbasis Mikrokontroler - Suhaebri, Tino; Ainuddin, Asma; Agustiawan, Aan; Pratama, M. Rezaldi; Wahyuni, Sri (Jurnal Mosfet, 2024)
The large amount of scattered cans in the environment causes a decline in aesthetics and poses a potential risk of injury when these cans are stepped on or hammered to reduce their volume. This study aims to design and build an Arduino-based can press that can reduce the volume of aluminum cans from 11.6 cm to 4 to 5 cm safely and efficiently. The methods used include literature review, frame design, electrical circuit design, and software development to control the pressing process. Tests were conducted on the sensor, voltage, current, and pressing results. The test results show that the infrared sensor detects cans at a distance of 1 to 11 cm, and the stepper motor activates when the sensor detects a can, stopping when the activation delay ends and immediately reversing the motor’s direction. The average pressing time is 7.9 seconds, with a pressing capacity of up to 455 cans per hour. The power used during pressing is 56.5 W, with an energy consumption of 0.0565 kWh for 455 cans. In conclusion, the designed can press works well, reduces can volume efficiently and safely, and has the potential to reduce environmental can waste with good energy efficiency.